Student’s Perceptions of the Role of Politeness in Online Communication - Meiratnasari, Ayu; Wijayanto, Agus; Suparno, Suparno (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
English has the primary role as a communicationtool in industrial revolution 4.0 because it was aninternational language. In this era, the developments oftechnologies facilitated people around the world tocommunicate through social media, email, website, andothers. Through those communications, they can enhancetheir business, developing their studies, or expanding theirrelations. However, every country has its norms inconversation, so that politeness strategies are the corecomponent in achieving the successfulness ofcommunications. This study was one of qualitative researchwhich primarily focuses on exploring the student'sperceptions on the role of politeness strategies in usingEnglish in online communication. The data was collected bydelivering the questionnaire to the 40 students in SMANegeri 1 Kretek Bantul, Yogyakarta, Indonesia, andinterviews with some of them. The data of this study wereanalyzed using a content analysis approach. The resultsdescribed that the students consider politeness strategies astheir policies during the communications. The implicationsof this study were to help the teachers identify the student'sneed in the development of politeness strategies and toprevent miscommunication during the onlinecommunication process